EFEKTIVITAS MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR MATEMATIKA MATERI BANGUN DATAR PADA SISWA KELAS V SEKOLAH DASAR - Ryanjani Lila Anggraita; Sri Wahyuni; Dyah Arti Mumpuni; Budi Murtiyasa; Sumardi, Sumardi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to examine the effect of using the Contextual Teaching and Learning (CTL) learning model on mathematics learning outcomes for class V elementary school mathematics. This research is quantitative research with experimental methods. The research design used is  control group pre-test post-test design. The subjects of this research were 25 fifth-grade students of SDN 01 Jati, Jaten, Karanganyar. The experimental class consisted of 13 people and the control class consisted of 12 people. Data collection was carried out using instruments in the form of description questions, data analysis using the paired sample t-test and prerequisite tests, namely the normality test and homogeneity test with the help of the SPSS version 16 program. Based on the results of the t test using the Paire Sample T-test, a sig value was obtained. 2-tailed) of 0.000< 0.05. So the hypothesis Ha is accepted and Ho is rejected, meaning that the CTL learning model in mathematics learning material about flat figures has a significant effect on the learning outcomes of fifth grade elementary school students.